MSME BUSINESS TRAINING PROGRAM FOR MAKING BAGS FROM PANDAN LEATHER AND WOVEN TO INCREASE THE INCOME OF THE COMMUNITY IN VILLAGE KESATUAN PERBAUGAN DISTRICT, SERDANG BEDAGAI REGENCY - Dewi Sundari Tanjung; Suriana; Jihan Hidayah Putri; Porkas Sojuangon Lubis; Rodi Syafrizal; Evida Rahimah; M.Tohir Ritonga (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This community service program aims to improve the skills, creativity, and economic independence of the community in Kesatuan Hamlet II Village, Perbaungan District, Serdang Bedagai Regency, especially for women who are housewives and school dropouts. The activity was carried out through training in making bags from leather and woven pandan leaves that combine traditional and modern motifs. The implementation method used a participatory approach with the principle of adult learning, which involved stages of socialization, demonstration of bag-making techniques, online marketing training, and collaboration with the village government and related institutions. The results of the activity showed a significant increase in the participants' understanding and skills regarding environmentally friendly bag production techniques and entrepreneurial awareness. Based on the results of the questionnaire, the majority of participants stated that this activity was beneficial and desired to continue the business independently. This program not only increases community income but also encourages the preservation of local culture through crafts based on local natural resources. Thus, this training makes a significant contribution to the development of creative MSMEs, women's empowerment, and strengthening the sustainable economy at the village level.